Fabrication and characterization of passivated metallic nanowires through nanoporous AAO template - Seah, Geok Leng. (2010)
One-dimensional (1D) nanowires have attracted much attention recently due to their unique physical (electrical, optical, thermal and magnetic) properties. Their applications range from electronic devices to sensoring and cooling system. In the area of microelectronics, copper nanowires are explored as it has good electrical and mechanical properties. Moveover, it is cheap and has high resistance to electromigration. However, copper oxidizes readily in air to form oxides, especially in the form of nanowires when aspect ratio is high. Oxidation of copper can cause changes in mechanical as well as electrical properties. This project proposed to passivate copper nanowires by forming a sheath/core (silica/copper) nanostructure with gold tips. By doing this, characterization such as electrical testing can be done on individual passivated copper nanowires. Gold tips (nanowires) were synthesized via electrodeposition while silica nanotube was fabricated using surface sol-gel (SSG) method. Both were achieved by using anodized aluminium oxide (AAO) membrane as the template. Optimum conditions to electrodeposit gold nanowires were at -1.2V and 60 °C using cyanide base precursor, producing high density of polycrystalline nanowires with preferred orientation growth in [111] direction. On the other hand, SSG experimental procedures were improved by etching unwanted silica layer away from the AAO template surface after every SSG cycle. This undesired silica layer prevented SiCl4 precursor from entering the pores after each cycle. In addition, it impedes copper electrodeposition after the experiment. With the additional step of etching introduced, silica nanotubes with an average wall thickness of 15 nm were obtained.